Recycling Bio-Based Wastes into Road-Base Binder: Mechanical, Leaching, and Radiological Implications - B. Peceño; S. Hurtado-Bermudez; B. Alonso-Fariñas; M. Villa-Alfageme; J. L. Más; C. Leiva (Applied Sciences, 2023)
This work presents a physical, mechanical, durability, leaching, and radiological assay of three wastes (egg and scallop shells and olive pomace ash) as road-base binders. Two different waste/Portland-cement ratios (7.5/92.5 and 80/20) were studied. Density and compressive strength decreased when different wastes were added in every proportion. Additions of 7.5% of both shells reduce the density to about 2.5% and the compressive strength to 20%, while 80% reduces the density to 20% and the compressive strength to 90%, while the addition of biomass fly ash decreases the density and compressive strength in a higher proportion than shells. The durability against acid attack is increased when the three wastes are used, and this increase is higher when the waste dosage is increased (up to 15 times more when 80% biomass ash is used). With respect to leaching, scallop and eggshells can be used as a component of hydraulic road binder, but olive pomace ash presents leaching values higher than the limits of different regulations (Se, Pb, Ni, Mo, Cu, and As). From a radiological perspective, all road-base binders present an activity concentration index lower than 1, except when olive pomace ash was used, and the binders showed higher values of 40K due to the high potassium content of fly ash.